Clarifying the type of the polyphyletic genus Schizachyrium (Poaceae: Andropogoneae) - Welker, Cassiano A. D. (2021)
Schizachyrium Nees is one of the largest genera of the grass tribe Andropogoneae and is clearly polyphyletic, including at least three distinct lineages. For more than a century, the type of Schizachyrium has been the subject of disagreement in the literature, with most authors considering it to be S. brevifolium (Sw.) Nees ex Buse, but others accepting S. condensatum (Kunth) Nees. Our investigation confirmed that the earliest effective typification of Schizachyrium was performed by Pfeiffer (1874) and thus S. condensatum is the correct type of the genus. Elucidation of this issue is crucial for the future taxonomic rearrangements of this polyphyletic genus since its type will define which lineage will retain the generic name Schizachyrium.